The Effect of The Pelvic Rocking Technique on The Duration of The Active Phase of The First Stage of Labor in The Working Area of Kalapanunggal Health Center - Rini Indriani; Lisa Trina Arlym; Rukmaini (International Journal of Midwifery and Health Sciences, 2025)
Introduction: Prolonged active phase of labor increases the risk of maternal and neonatal complications. One non-pharmacological method to accelerate labor is the pelvic rocking technique using a birthing ball. Objective: To determine the effect of pelvic rocking on the duration of the active phase of the first stage of labor in the working area of Kalapanunggal Health Center. Methods: A quasi-experimental study with a two-group posttest-only design was conducted on 30 women in labor, divided into an intervention group (pelvic rocking, n=15) and a control group (light walking, n=15) selected by purposive sampling. Instruments included partographs and observation sheets. Data were analyzed using the Mann-Whitney test. Results: Most respondents were aged 20–35 years (66.7%) and primiparous (56.7%). The mean duration of the active phase of the first stage was 221 minutes in the intervention group and 390 minutes in the control group (p=0.000). The mean duration of the second stage was 77 minutes in the intervention group and 108 minutes in the control group (p=0.021). Conclusion: Pelvic rocking significantly shortens the duration of both the active phase of the first stage and the second stage of labor. This technique can be recommended as an effective and easily applied non-pharmacological intervention to support labor progress.